Analisis Perencanaan Pajak Untuk Meminimalkan Beban Pajak Penghasilan (Pph) Pada Pt Maju Utama Raya Indonesia - Maesaroh, Siti -; Mahpudin, Endang (Peneliti.net, 2023)
This study aims to analyze tax planning on income tax expense at PT Maju Utama Raya Indonesia. The study used a quantitative method with a descriptive approach and the number of observations on corporate income tax for PT Maju Utama Raya Indonesia for 4 years. In 2019 income tax article 25 amounted to IDR 145,026,218.00 to IDR 103,256,426.00 and previously the income tax article 29 was underpaid by IDR 7,381,351.00 to overpaid income tax of IDR 34,353,347.00. In 2020 income tax of IDR 91,064,503.00 becomes IDR 75,042,979.00, and previously the income tax article 29 was overpaid by IDR 53,961,715.00 to overpaid income tax of IDR 71,982,239.00. In 2021 income tax of IDR 93,944,590.00 becomes IDR 90,002,932.00 and previously underpaid income tax article 29 of IDR 2,880,087 became underpaid income tax of IDR 1,061,571.00. In 2022 income tax of IDR 226,489,940.00 becomes IDR 178,362,882.00 and previously underpaid income tax article 29 of IDR 132,543,349.00 became underpaid income tax of IDR 84,418,292.00. The emergence of overpaid income tax as a result of planning by making business travel expenses a deduction from gross income in accordance with Article 6 paragraph 1 of the Income Tax Law, and in 2022 Kitchen and Consumption accounts as Natura enjoyment can be included as a deduction expense for gross income which reduces expenses income tax in accordance with the latest government regulation No. 55 Year 2022. Keyword : Tax Planning, PPh, Taxes.